Cobalt salophen functionalized SBA-15 as an active catalyst for photocatalytic water oxidation. Issue 17 (3rd February 2016) - Qu, Lingling; Cai, Jia; Chen, Qiuyun
Abstract : A new cobalt salophen functionalized SBA-15 is the cost-effective photocatalyst for water oxidation under mild conditions. Abstract : Design and synthesis of highly efficient and cost-effective catalysts for water oxidation is one of the biggest challenges that chemists are facing today. The low-cost salophen cobalt complex represents a promising water oxidation visible-light-photocatalyst under neutral conditions. To avoid degradation and improve the photocatalytic activity of cobalt salophen, we have synthesized a cobalt salophen-based organic–inorganic hybrid mesoporous material (MC) via grafting cobalt salophen into mesoporous SBA-15 for water oxidation under mild conditions. MC is found to be more active and stable than the neat salophen cobalt. Under similar conditions, MC shows a significantly higher activities (turnover frequency: 59.64 mol of O2 h −1 mol Co −1 ) than the corresponding cobalt complex (turnover frequency: 2.520 mol of O2 h −1 mol Co −1 ). After being used four times, the reactivity and the yield of oxygen for MC is still 10 times higher than pure salophen cobalt. MC could be considered as a promising catalyst for water oxidation.